Pengaruh Inflasi Dan Bi Rate Terhadap Pembiayaan Modal Kerja Pada Bank Umum Syariah - Uswatun Khasanah; Abd Wahab; Samsul Samsul (CV. ITTC INDONESIA, 2025)
Factors influencing customer decisions in choosing working capital financing in Islamic commercial banks include inflation and the BI Rate. Rising inflation can reduce the amount of funds that Islamic banks can collect for financing, while high financing r isks may limit the distribution of funds to the real sector. This study aims to analyze the effect of inflation and the BI Rate on working capital financing in Islamic commercial banks in Indonesia for the 2019–2023 period. The research uses a quantitative method with secondary time series data and path analysis through SPSS 21. The results show that inflation has a positive and significant effect on working capital financing, while the BI Rate has a positive but insignificant effect. Simultaneously, both variables have a positive and significant influence. These findings have important implications for business actors to better understand the macroeconomic dynamics that affect financing, enabling more strateg ic financial decision-making.